Portfele akcji z ustalonym porządkiem oczekiwanych stóp zwrotu - Romowicz, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper presents a method for portfolio optimization based on ordering information about expected returns of stocks in portfolio. This method extends Markowitz' mean variance optimality condition. It can be useful in many cases -for instance, when assets are divided into multiple sectors or when investor has information about every asset in his portfolio (in a way of sorting them in order of their beliefs about it). In case that beliefs vector is more complicated, heuristic methods like Monte Carlo or Genetic Algorithm can be used. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 354-359